2017
DOI: 10.1111/vde.12416
|View full text |Cite
|
Sign up to set email alerts
|

The future of immunotherapy for canine atopic dermatitis: a review

Abstract: Allergen specific immunotherapy (ASIT) is a foundation treatment for canine atopic dermatitis (CAD), though few critical studies have documented its effectiveness as a disease-modifying treatment in dogs. The mechanisms by which ASIT works in dogs have not been elucidated, although they are likely to parallel those known for humans. Current ASIT approaches in CAD focus on either subcutaneous or sublingual administration. Greater knowledge of major allergens in dogs, ideal dosage regimes and details of allergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
0
24
0
2
Order By: Relevance
“…Using recombinant allergens such as Dermatophagoides farinae allergen (Der f 2) [ 149 , 150 ] may result in more reproducible results and a higher success rate compared to standard AIT and ILIT [ 151 ]. Modified allergen preparations such as allergoids, allergen peptides as well as alteration with adjuvants may decrease the risk of adverse effects and increase efficacy [ 152 ]. First studies evaluated bacterial oligodeoxynucleotides in canine AD [ 79 , 107 ] with promising results.…”
Section: Unmet Needs and Researchmentioning
confidence: 99%
“…Using recombinant allergens such as Dermatophagoides farinae allergen (Der f 2) [ 149 , 150 ] may result in more reproducible results and a higher success rate compared to standard AIT and ILIT [ 151 ]. Modified allergen preparations such as allergoids, allergen peptides as well as alteration with adjuvants may decrease the risk of adverse effects and increase efficacy [ 152 ]. First studies evaluated bacterial oligodeoxynucleotides in canine AD [ 79 , 107 ] with promising results.…”
Section: Unmet Needs and Researchmentioning
confidence: 99%
“…This is in discordance with many specialists' beliefs and previously published data. 5 Reasons for the discordance in perception of ASIT efficacy may be due to differences in the definition of "successful" therapy, the expectation that ASIT will ameliorate the need for all concomitant therapy, or a lack of understanding about the expected timeline for improvement following initiation of ASIT. Specialist outreach to the referring community through continuing education and training events provides an excellent opportunity for dermatologists to reach the referring population, build their referral network, and increase awareness of the benefits of ASIT and options for dermatological immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Allergen-specific immunotherapy (ASIT) is the only therapeutic option with the ability to reduce clinical signs of atopic dermatitis (AD) and potentially prevent progression of disease by modifying or reversing its pathogenesis. [5][6][7] Various studies have demonstrated ≥50% amelioration in severity of clinical signs, with decreased incidence of secondary yeast and bacterial infections in 60-72% of dogs with cAD. [5][6][7][8][9][10] Compared to a lifetime of systemic medications with potential for unintended adverse effects, ASIT protocols can be tailored to induce tolerance in most animals with minimal long-term risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allergen specific immunotherapy (ASIT) is still considered the best long-term approach for young animals with symptoms present for many months/years [ 44 ]. Although allergen-specific immunotherapy is typically presented as “expensive”, when compared to the cumulative cost of other forms of management (e.g., cyclosporine in a large-breed dog) it is actually cost effective, as it can decrease the frequency of infections and, therefore, reduce the use of antibiotics and the risk of resistance, as well as the need for other medications.…”
Section: Clinical Management Of Canine Admentioning
confidence: 99%